Study of the partition of sodium diclofenac and norfloxacin in aqueous two-phase systems based on copolymers and dextran - Ahsaie, Farzaneh Ghazizadeh (2020)
The partitioning behavior of norfloxacin (more hydrophilic) and sodium diclofenac (more hydrophobic) was studied considering the use of aqueous two-phase systems (ATPSs) based in copolymers and dextran. For this research, the phase behavior of systems composed of water, a copolymer (Pluronic PE6400, Pluronic L35, Pluronic PE6800, PEG-ran-PPG monobutyl ether and PEG-ran-PPG) and dextran (Mw=40000 and 6000 g.mol−1) were investigated. The phase diagrams showed that by increasing the molecular weight and the copolymer PPG/PEG ratio, the biphasic region is enlarged. After defining the bionodal curves, a preliminary screening on the partition of two pharmaceutic ingredients (sodium diclofenac and norfloxacin) was carried. After selected the most appropriate ATPS for the partition of both drugs, namely systems based on diblock copolymers (poly(ethylene glycol)-poly(propylene glycol)) – dextran T6 and one random copolymer (poly(ethylene glycol)-ran-poly(propylene glycol)) – dextran T6, the effect of the copolymer concentration and different mixture points was assessed. In the end, the results showed that by increasing the copolymer concentration and tie-line length, the partition coefficient of the pharmaceutical ingredients increased in the block copolymer-based ATPS and decreased in systems containing the random copolymer